Identification of Gene Markers in Aflatoxin-Resistant Maize Germplasm for Marker-Assisted Breeding - Brown, Robert L.; Menkir, Abebe; Chen, Zhi-Yuan; Luo, Meng; Bhatnagar, Deepak (IntechOpen, 2011)
None